Manifestation of bronchial hyperreactivity from exposure to heavy and precious metal vapors among the ore smeltery workers of Zveçan, Kosovo - Saudin Maliqi; Pellumb Islami; Ali Iljazi; Hilmi Islami (Wolters Kluwer Medknow Publications, 2021)
Context: Kosovo is a region in the Western Balkans that is rich in minerals and coal, so pollution is a serious public health problem there. Workers in the heavy and precious metal smeltery in Zveqan, Kosovo, were studied with regard to the roles that vapor from the smelting of metals (Pb, Zn, Au, Ag, P, and Cu) and particulate matter play in causing bronchial hyperreactivity. Objectives: The purpose of the article was to measure the parameters of lung function as determined by body plethysmography, diagnosis of respiratory diseases, and assessment of respiratory function using a histamine bronchoprovocation test. Settings and Design: The present study was conducted in two groups of participants: A control group, which included 25 healthy persons, and a smeltery worker group, which included 45 mine workers (15 smokers and 30 nonsmokers) holding permanent jobs in the mineral foundry of Zvecan, Kosovo. Subjects and Methods: Pulmonary function parameters (specific airway resistance [Raw] and intrathoracic gas volume) were measured and used to calculate the specific resistance (SRaw)and specific conductance (SGaw) of the airways, and a histamine bronchoprovocation test was conducted. Statistical Analysis Used: The data were entered and analyzed using the Microsoft Excel and INSTAT 3 software. Results: Airway specific resistance (SRaw) was significantly higher in the smeltery worker group (P < 0.01) as compared to the control group (P > 0.1). Conclusion: These results suggest that occupational exposure to vapors during the metal refining process poses a risk to the workers' health and can cause bronchial hyperreactivity, bronchial asthma, or chronic obstructive pulmonary disease.